The tree house mystery. - York, Carol (Beach); Lonette, Reisie (New York, Coward, McCann & Geoghegan, 1973)
From the day they move to their new house in the country, Roger and Anabelle have a strange feeling about the tree house on their property.
Keywords: Mystery and detective stories